Case of Tinea Corporis on The Back Treated with Topical Terbinafine - Idris, Irma Suryani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Dermatophytes, which are fungi that grow on keratin, are the cause of tinea corporis, a superficial fungal infection of the skin of the body (apart from the scalp, face, and groin). At the dermatovenereology polyclinic of a Makassar hospital, a 19-year-old teen was diagnosed with tinea corporis. The diagnosis was made based on clinical features, direct microscopic examination (10% KOH). Long, branched hyphae with some hyphae starting to separate. The patient was treated with topical terbinafine and clinical and mycological improvement. Therapy was continued with topical terbinafine for a month. Terbinafine is a fungicidal antifungal drug that works by inhibiting ergosterol biosynthesis. Patients treated topically were given topical terbinafine applied twice a day. Without ergosterol, the fungal cell membrane is damaged and cell function is disrupted, causing fungal death. Terbinafine is the first line for tinea corporis and cruris, because it is more effective and has a shorter treatment duration than ketoconazole or other azoles. The results of this case examination after 14 days of treatment showed improvement, negative KOH results, clinical symptoms such as itching were greatly reduced and topical medication was continued. The patient was asked to come for a check-up, treatment continued until the lesions on the back disappeared.